2023
DOI: 10.3390/v15061247
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences and Characterization of Chicken Astrovirus and Avian Nephritis Virus from Tanzanian Live Bird Markets

Abstract: The enteric chicken astrovirus (CAstV) and avian nephritis virus (ANV) are the type species of the genus Avastrovirus (AAstV; Astroviridae family), capable of causing considerable production losses in poultry. Using next-generation sequencing of a cloacal swab from a backyard chicken in Tanzania, we assembled genome sequences of ANV and CAstV (6918 nt and 7318 nt in length, respectively, excluding poly(A) tails, which have a typical AAstV genome architecture (5′-UTR-ORF1a-ORF1b-ORF2-‘3-UTR). They are most simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…The two genomes have the typical AAstV architecture (5′-UTR-ORF1a-ORF1b-ORF2-′3-UTR) and classify with Eurasian CAstV antigenic group Aii (CAstV-Aii) and ANV group 5 (ANV-5) with the CAstV-Aii being a recombinant of CAstV-Bi and Bvi. We have recently published the genomic data of the two Tanzanian AAstVs in a separate paper ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two genomes have the typical AAstV architecture (5′-UTR-ORF1a-ORF1b-ORF2-′3-UTR) and classify with Eurasian CAstV antigenic group Aii (CAstV-Aii) and ANV group 5 (ANV-5) with the CAstV-Aii being a recombinant of CAstV-Bi and Bvi. We have recently published the genomic data of the two Tanzanian AAstVs in a separate paper ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two complete genome sequences of IBVs (27,686 and 27,663 nt in length) were assembled from OP samples of chickens swabbed at central and Buguruni LBMs in Arusha and Dar es Salaam regions, respectively (Table 4). Further analyses showed that one of the IBVs (strain 2,145-CA127; GenBank accession number OQ725698) is a recombinant virus with a backbone derived from an LX4-like IBV (lineage GI-19) virus and a turkey CoV-like S-gene; We have recently published the sequence data of this recombinant strain in a separate paper (66).…”
Section: Viruses Coinfecting With Ndvsmentioning
confidence: 99%
“…The DAstV-3, DAstV-4, GoAstV-1, GoAstV-2 are four new AAstVs in recent years, which have not been formally classified by ICTV, and cause duck hepatitis, goose gout and urate deposition, and the healthy development of China’s poultry farming industry poses a certain danger ( Donato and Vijaykrishna, 2017 ). At the same time, the disease’s host diversity means there is a potential risk of intra−/cross-species transmission, and there is no commercial vaccine or targeted drug against the disease, making it difficult to prevent and control ( Cortez et al, 2017 ; Kariithi et al, 2023 ). DAstV-3, DAstV-4, GoAstV-1 and GoAstV-2 are four waterfowl astroviruses reported since 2014, which can cause symptoms such as enteritis, hepatitis, urate deposition and gout, and have caused some economic losses to the healthy development of China’s waterfowl aquaculture industry since their discovery ( Liao et al, 2015 ; Liu et al, 2016 , 2022 ; Zhu and Sun, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, untargeted next-generation sequencing (NGS) technology has been increasingly employed for the detection and characterization of RNA viruses, particularly in the context of avian diseases ( Chen et al, 2013 ; Tang et al, 2015 ; Goraichuk et al, 2016 , 2017 , 2019 , 2021a , b ; Croville et al, 2018 ; Ferreri et al, 2019 ; Tal et al, 2019 ; Patzina-Mehling et al, 2020 ; Crossley et al, 2021 ; Chrzastek et al, 2022 ; Damir et al, 2023 ; Ip et al, 2023 ; Kariithi et al, 2023 ; Techera et al, 2023 ). Avian viruses, including highly pathogenic avian influenza virus (AIV) and Newcastle disease virus (NDV), pose significant threats to poultry populations and public health ( Alexander, 1998 ; Suarez, 2017 ; Swayne et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%